PENINGKATAN HASIL BELAJAR SOSIOLOGI MATERI GLOBALISASI MELALUI PENERAPAN STRATEGI PENGORGANISASIAN PETA KONSEP (CONCEPT MAPPING) SISWA KELAS XII IPS 1 SMA NEGERI 1 MERANGIN TAHUN 2021/2022 - Marya Setiawati, S.Sos (LP3M | STKIP YPM Bangko, 2022)
This study aims to determine the improvement of students' Sociology learning outcomes through the application of concept mapping strategies. The method used in this research is Classroom Action Research. The data collection techniques in this study were: classroom observation, interviews, distributing questionnaires, formative evaluations, and discussions with partner teachers (collaborators). The results of the first cycle of action showed that 67% or 22 of 33 students had shown an increase in learning outcomes by achieving the KKM score (≥ 70), and in the second cycle it increased significantly to 91% or 30 of 33 students had achieved the KKM score (≥ 70). . These conclusions are reinforced by the results of the student opinion questionnaire about learning with concept maps which shows that in the first cycle there are 14 of 33 students or 42.5% of students stating that learning with concept maps is quite helpful in learning Sociology of globalization material and 11 of 33 students stated that learning with concept maps is good in helping to learn Sociology of globalization material. While in cycle II there were 16 of 33 students or 48.5% of students stated that learning with concept maps was good in helping to learn Sociology of globalization material and 5 of 33 students or 15.2% stated that learning with concept maps was very good in study Sociology on the subject of globalization